Connections to specialized knowledge of Biology teachers on High School subjects (Research, Society and Development, 2021)
From the perspective of researching the knowledge base of teachers, the discipline of Biology was the pioneer among the sciences to develop a model of specialized knowledge of teachers transposed from the model of Specialized Knowledge of Mathematics Teachers, the model of Specialized Knowledge of Mathematics Teachers. Biology (BTSK). However, our objective was to identify the connections of the specialized knowledge of Biology professors and to promote an integrated view of the relationships between the subdomains presented in the model and that, in order to reach our objective, we used PaP-eR (Professional and Pedagogical Experience Repertoire) as an instrument of analysis. ) that reported teaching practices with content of cytology, respiratory system and ecological interactions, configuring a qualitative research in which our results allowed us to describe an integrative view of knowledge connections and understand how all knowledge articulated to promote more knowledge. expressive and grounding mobilized in the report of high school practices.